RELIGIOUS COMMUNICATIONS AND ENVIRONMENTAL RESPONSIBILITY OF MODERN MAN - Skyba, Oksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
under religious communications influence, which is relevant in a difficult ecological situation. The aim and tasks Today the problem of forming of environmental responsibility is becoming one of the most important, and religion makes contribution into its solution. Research methods. The theoretical and methodological basis of the study are general and special methods and approaches that allow one to trace and take into account important aspects of the formation and development of man’s environmental responsibility caused by religious communications. Research results. The global environmental problem of mankind has become the focus of scientists in the late XX and early XXI centuries. Scientists have begun to realize the need to change man’s attitude to nature and their responsibility for the possible negative consequences of their discoveries, abandoning those areas of work that can bring disaster. Significant influence on the formation of new values, the environmental responsibility of man was exerted by ecological ethics, bioethics and others. Religion today also condemns consumer ideology, which denies the independent value of nature, viewing it only as a source of resources to meet ever-increasing material needs. Thus, humanity is taking the first steps in reorienting to the idea of integral harmonious coexistence of man and nature. Discussion. Since the second half of the XX century, ecology goes beyond biology and becomes one of the foundations of modern knowledge and education. The reason for such changes is man’s awareness of the global environmental crisis, which is not so much a negative change in the natural environment, but undermining the ability of the biosphere to self-healing. Therefore, all areas of society must take into account the aspect of the relationship between society and the biosphere, as evidenced by the emergence of new directions in ecological knowledge, such as the ecology of settlements, the ecology of cultures and even the ecology of religion. Conclusion. Today the people have realized that the change of ecological paradigm is not just a condition for the further development of human civilization, but the physical survival of man. Religious communications play a role in improving the ecological consciousness of modern man.